2009
DOI: 10.1007/s11270-009-0136-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Waters Containing the Thiocarbamate Herbicide Molinate through an Adsorption/Bio-Regeneration System using a Low-Cost Adsorbent

Abstract: The feasibility of using recycled granular tire rubber (GTR) to remove molinate from contaminated water bodies was evaluated in this study. Adsorption equilibrium data was well described by a linear isotherm, and the adsorption was completely reversible. Breakthrough curves showed column efficiencies of approximately 40%, based on total capacity, and complete bed regeneration was achieved using clean water. The effluent from the regeneration step was successfully decontaminated using a defined bacterial mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In our study, this was not a limitation, as in previous work we established a fivemember bacterial mixed culture (named DC) with constitutive capacity to mineralize molinate (Barreiros et al 2003(Barreiros et al , 2008. Culture DC is able to promote molinate degradation under a wide array of abiotic conditions (Carvalho et al 2010;Coelho et al 2006;Silva et al 2004b), without the accumulation of any toxic metabolites (Correia et al 2006). Thus, in the current study we aimed at assessing the ability of culture DC to remove the pesticide from floodwaters, and inferring at the possible perturbations this culture could induce in the autochthonous community.…”
Section: Introductionmentioning
confidence: 96%
“…In our study, this was not a limitation, as in previous work we established a fivemember bacterial mixed culture (named DC) with constitutive capacity to mineralize molinate (Barreiros et al 2003(Barreiros et al , 2008. Culture DC is able to promote molinate degradation under a wide array of abiotic conditions (Carvalho et al 2010;Coelho et al 2006;Silva et al 2004b), without the accumulation of any toxic metabolites (Correia et al 2006). Thus, in the current study we aimed at assessing the ability of culture DC to remove the pesticide from floodwaters, and inferring at the possible perturbations this culture could induce in the autochthonous community.…”
Section: Introductionmentioning
confidence: 96%
“…The feasibility of using recycled GTR to remove molinate from contaminated water bodies was evaluated (Carvalho et al, 2010). It was found that GTR can be used in a cost-effective treatment system in which molinate is removed from polluted water by adsorption, and the spent adsorbent is regenerated with fresh water.…”
Section: Waste Tirementioning
confidence: 99%